2018
DOI: 10.1016/j.jnutbio.2017.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Marine fish oil is more potent than plant-based n-3 polyunsaturated fatty acids in the prevention of mammary tumors

Abstract: Marine-derived n-3 polyunsaturated fatty acids (PUFAs), such as eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), have been shown to inhibit mammary carcinogenesis. However, evidence regarding plant-based α-linolenic acid (ALA), the major n-3 PUFA in the Western diet, remains equivocal. The objective of this study was to examine the effect of lifelong exposure to plant- or marine-derived n-3 PUFAs on pubertal mammary gland and tumor development in MMTV-neu(ndl)-YD5 mice. It is hypothesized that lifel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 48 publications
1
38
0
Order By: Relevance
“…In this study, according to the MTT assay (Figure 1), the extracted FA from all the tested macroalgae showed antitumor activity against both cells, and the inhibition was lower for the non-tumoral CHO cell line than for the breast cancer cell lines MCF-7 and MDA-MB-231. Previous in viv o and in vitro studies on breast cancer cell lines have shown that n -3 PUFA may be effective in reducing cell growth, reducing tumor volume and preventing metastasis, among other benefits, by multiple mechanisms such as influences on transcription factor activity, gene expression, and signal transduction; the alteration of estrogen metabolism; alterations in the production of free radicals and reactive oxygen species; the suppression of neoplasic transformation; the inhibition of cell growth; increased apoptosis; and the inhibition of eicosanoid production from n -6 FA precursors (Larsson et al, 2004; Wannous et al, 2013; Liu et al, 2018). The FA tested in this study resulted in little or no cytotoxicity against the CHO cell line at concentrations up to 100 μg/mL.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, according to the MTT assay (Figure 1), the extracted FA from all the tested macroalgae showed antitumor activity against both cells, and the inhibition was lower for the non-tumoral CHO cell line than for the breast cancer cell lines MCF-7 and MDA-MB-231. Previous in viv o and in vitro studies on breast cancer cell lines have shown that n -3 PUFA may be effective in reducing cell growth, reducing tumor volume and preventing metastasis, among other benefits, by multiple mechanisms such as influences on transcription factor activity, gene expression, and signal transduction; the alteration of estrogen metabolism; alterations in the production of free radicals and reactive oxygen species; the suppression of neoplasic transformation; the inhibition of cell growth; increased apoptosis; and the inhibition of eicosanoid production from n -6 FA precursors (Larsson et al, 2004; Wannous et al, 2013; Liu et al, 2018). The FA tested in this study resulted in little or no cytotoxicity against the CHO cell line at concentrations up to 100 μg/mL.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, n-3 PUFAs were shown to decrease tumor growth and ability of tumors to metastasize. It is perceived that the observed effects may be attributed to their influence on gene expression, transcription factors, and suppression of neoplastic stimulations, and to their ability to influence the production of ROS, cell metabolism and induce apoptosis (24,25,26). Fatty acids were also shown to enhance the effectiveness of standard chemo-or radiotherapy (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…The same is true for the production and intake of intermediate n-3 LC-PUFA, such as docosapentaenoic acid (DPA), the effects and mechanisms of action of which are poorly understood [ 4 ]. With regard to cancer risk in particular, evidence suggests a limited role of ALA in reducing development of various tumor types, yet greater biopotency of preformed DHA and EPA in a variety of pathways related to cancer risk reduction [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%